Decomposition of Gender Differentials in Agricultural Productivity in Ethiopia - Aguilar, Arturo; Carranza, Eliana; Goldstein, Markus; Kilic, Talip; Oseni, Gbemisola (World Bank, Washington, DC, 2014)
This paper employs decomposition methods to analyze differences in agricultural productivity between male and female land managers in Ethiopia. It employs data from the 2011-2012 Ethiopian Rural Socioeconomic Survey. An overall 23.4 percent gender differential in agricultural productivity is estimated at the mean in favor of male land managers, of which 10.1 percentage points are explained by differences in land manager characteristics, land attributes, and unequal access to resources (the endowment effect). The remaining 13.4 percentage points are explained by unequal returns to productive components, but cannot be easily tied to specific covariates. These results are mainly driven by non-married female managers (mainly single and divorced). Married female managers do not display such disadvantages. Further analysis along the productivity distribution reveals that gender differentials are more pronounced at mid-levels of productivity and that the share of the gender gap explained by the endowment effect declines as productivity increases. Detailed decomposition of estimates at selected points of the agricultural productivity distribution provides valuable information for policy intervention purposes.